Exegetical Translation of the Qur'an: An Action Research on Prospective Islamic Teachers in Indonesia - Abdussalam, Aam; Supriyadi, Tedi; Supriadi, Udin; Saepudin, Aep; Pamungkas, Muhamad Imam (Indonesian Journal of Applied Linguistics, 2021)
To accomplish the mission of spreading the message of the Quran, prospective Islamic teachers need to be equipped with the ability to translate the Qur'an. However, in reality, they face difficulties in understanding the messages of the Qur'an because of their low Arabic language skills. This research aims to find practical steps to improve the competence of prospective Islamic teachers in translating the Qur'an. This research involved 35 prospective Islamic teachers, consisting of 20 men and 15 women from various districts at a tertiary institution in West Java Indonesia. Data were collected using surveys, observations, and semi-structured interviews. Data were thematically identified, coded, evaluated, categorized, and analyzed using the analytical tool of content analysis. This research produced six learning steps (summarized in an acronym TARJIM as developed from the Tamyiz method). The Tamyiz method was a hypothetical model that was used as the foundation of this action research. These steps were able to improve the ability of prospective Islamic teachers in translating the Qur’an from the beginner level to the skilled level as many as 27 (77.14%) participants, from the basic level to the skilled level as many as five (14.28%) participants, and from the basic level to advanced level as many as three (8.57%) participants. Moreover, the six steps provided skills for the prospective teachers in translating the Qur'an verses that have exegetical nuances. The findings show that the six steps were effective steps to increase the competence of translating the Qur'an for prospective teachers of Islamic Religious Education.